Illustrating alternate endings through the use of sequential art as a tool for behavioral therapy for Filipino Adolescents with attention deficit disorder - Tantuico, Natalya Bernice Regina C.; San Valentin, Marc J. (2013)
ttention Deficit Hyperactivity Disorder or AD/HD is defined as a neurological conditiuon that is characterized by problems with inattention, impulse control and hyperactivity, and always seem to have an "on-the-go" type of attitude (Low, MA, 2010), and the subtype of this which is AD/HD predominantly Inattentive type or Attention Deficit Disorder (ADD) has symptoms of inattention and having trouble finishing tasks or following directions; hyperactivity is not present but sluggishness and lethargy are present instead, as well as the inability to process information at a normal pace (Low, MA, 2010). In the Philippines, the governing body taking charge of programs that cater to specifics groups of Filipinos like those who are persons with disabilities is the Department of Social Welfare and Development (DSWD); they conduct the National Disability Prevention and Rehabilitation Week every year in July in order to administer seminars and events about dealing and overcoming disabilities. Although there is the assumption that treatment of Attention Deficit Hyperactivity Disorder can be done through medical means alone, several studies have said that there are other aspects such as psychotherapy or behavioral therapy that should be involved as well (Hersen, 1986). This paper documents the effects of Attention Deficit Disorder on adolescents, the effectiveness and current methods and tools of behavioral therapy used in the Philippines, and examines the effects of comic strips on Filipino adolescents with Attention Deficit Disorder, as well as the suggested output in the form of comic strips that might be effective in administering behavioral therapy to adolescents with Attention Deficit Disorder in the Philippine setting. Usin qualitative data in the form of interviews with several licensed psychotherapists, developmental pediatricians and Special Education instructors who handle or who have experienced handling children and adolescents with Attention Deficit Disorder or Attention Deficit Htperactivity Disorder, as well as collating and analyzing secondary data from research materials involving the nature of ADD, behavioral therapy and sequential art, this study has been able to identify that (a) Attention Deficit Disorder is also known as the Inattentive type of Attention Deficit Hyperactivity Disorder, characterized by having no hyperactivity, and having more problems with focus or attention span; (B) Behavioral Therapy is adminsitered by trained therapists of Special Education teachers when there are visible behavioral signs and symptoms that impede a child's performance in school or interacting with peers, and also depending on the severity of the person's ADD or AD/HD; (c) children and adolescents with ADD or AD/HD perceive visual stimuli "normally" or the same way people without this disorder perceive visual stimuli and the use of visual materials is almost always included in the administration of behavioral therapy because they can stimulate the patient, and visual materials can be used as visual cues; (d) Comic strips would be useful in mediating information to patients with ADD or AD/HD because they incorporate the use of simpler visuals and text that may stimulate yet not distract the reader with ADD and AD/HD and (e) the use of colours or lines should be subtle--using light or calm colors, as to not distract the reader with ADD.
"April 2013"
Thesis (BFA)--University of the Philippines Diliman
Keywords: Interactive art -- Comic books, strips, etc. -- Philippines; Attention-deficit disorder in adolescence -- Philippines; Behavior therapy for teenagers -- Philippines